Bilinear Relational Neighborhood Model of the Stage of Diffusion of Sugar Production Based on the Heat Balance Equation - Shmyrin, A.M; Mishachev, N.M; Kanyugina, A.S (International Journal of Engineering and Technology, 2018)
In this paper, the problem of mathematical modeling of the stage of diffusion of sugar production is considered. To build the model, a combined approach is used: the structural identification based on the relational neighborhood scheme is refined with the help of the physical equation of the heat balance and then the parametric identification of the coefficients is performed using standard regression methods. The resulting model is bilinear.Â The corresponding model, resolved with respect to critically important temperature parameters, is fractional-bilinear. Parametric identification of the model is based on seasonal sampling of production data, the sample size is more than 10000.